Take control of expression: effector-mediated modulation of the host transcriptional machinery - Zuo, Weiliang; Xiao, Muye; Doehlemann, Gunther (Frontiers in Plant Science, 2026)
Interactions between plants and microbes that colonize them typically result in significant alterations of the host’s gene expression. Such transcriptional changes include modulation of immune responses, as well as orchestrating metabolic and developmental changes locally at sites of infection and systemically in the plant. Microbes colonizing diverse hosts have evolved cross-kingdom conserved mechanisms that utilize effectors to participate directly in host transcription process and actively rewrite its transcriptome for their own benefit. In this review, we highlight the mechanisms exploited by plant-colonizing microbes to manipulate the transcriptional machinery of their hosts, including interfering with and mimicking transcription factors and co-regulators. We provide a comprehensive overview of the functionalities of effectors beyond immune suppression and conclude that controlling the host transcriptome is crucial for establishing a favorable niche for microbial plant colonizers.